Determination of diclofenac in pharmaceutical preparations using a potentiometric sensor immobilized in a graphite matrix - Santini, A. O.; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Elsevier B.V., 2006)
The characteristics, performance, and application of an electrode, namely Pt| Hg|Hg-2(DCF)(2)|graphite, where DCF stands for diclofenac ion, are described. This electrode responds to diclofenac with sensitivity of (58.1 +/- 0.8) mV/decade over the range 5.0 x 10(-5) to 1.0 x 10(-2) Mol l(-1) at pH 6.5-9.0 and a detection limit of 3.2 x 10(-5) mol l(-1). The electrode is easily constructed at a relatively low cost with fast response time (within 10-30 s) and can be used for a period of 5 months without any considerable divergence in potentials. The proposed sensor displayed good selectivity for diclofenac in the presence of several substances, especially concerning carboxylate and inorganic anions. It was used to determine diclofenac in pharmaceutical preparations by means of the standard additions method. The analytical results obtained by using this electrode are in good agreement with those given by the United States Pharmacopeia procedures. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: diclofenac-sensitive electrode; potentiometry; pharmaceutical preparations